Sex- and age-dependent contribution of System xc– to cognitive, sensory, and social behaviors revealed by comprehensive behavioral analyses of System xc– null mice - Frare, Carla; Pitt, Shannon K.; Hewett, Sandra J. (Frontiers in Behavioral Neuroscience, 2023)
Background: System xc − (Sxc − ) is an important heteromeric amino acid cystine/glutamate exchanger that plays a pivotal role in the CNS by importing cystine into cells while exporting glutamate. Although certain behaviors have been identified as altered in Sxc − null mutant mice, our understanding of the comprehensive impact of Sxc − on behavior remains incomplete.Methods: To address this gap, we compared motor, sensory and social behaviors of male and female mice in mice null for Sxc − (SLC7A11 sut/sut ) with wildtype littermates (SLC7A11 +/+ ) in a comprehensive and systematic manner to determine effects of genotype, sex, age, and their potential interactions.Results: Motor performance was not affected by loss of Sxc − in both males and females, although it was impacted negatively by age. Motor learning was specifically disrupted in female mice lacking Sxc − at both 2 and 6 months of age. Further, female SLC7A11 sut/sut mice at both ages exhibited impaired sociability, but normal spatial and recognition memory, as well as sensorimotor gating. Finally, pronounced open-space anxiety was displayed by female SLC7A11 sut/sut when they were young. In contrast, young SLC7A11 sut/sut male mice demonstrated normal sociability, delayed spatial learning, increased open-space anxiety and heightened sensitivity to noise. As they aged, anxiety and noise sensitivity abated but hyperactivity emerged.Discussion: We find that the behavioral phenotypes of female SLC7A11 sut/sut are similar to those observed in mouse models of autism spectrum disorder, while behaviors of male SLC7A11 sut/sut resemble those seen in mouse models of attention deficit hyperactivity disorder. These results underscore the need for further investigation of SLC7A11 in neurodevelopment. By expanding our understanding of the potential involvement of Sxc − , we may gain additional insights into the mechanisms underlying complex neurodevelopmental conditions.